2016
DOI: 10.1111/den.12600
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of systematic training in the application of narrow‐band imaging international colorectal endoscopic (NICE) classification for optical diagnosis of colorectal polyps: Experience from a single center in China

Abstract: Systematic, feedback-based, training programs can help achieve high accuracy and good interobserver agreement in the application of the NICE classification for the prediction of the histology of colorectal polyps by endoscopists with different levels of experience.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 38 publications
0
12
0
1
Order By: Relevance
“…Recommendations suggest that training programs can help in achieving a high accuracy and good interobserver agreement in the use of AEITs such as NBI, and that it is a requirement for use in clinical practice [1, 2, 33, 86-88]. Even for simple NBI patterns in the stomach, a learning curve was observed, with a 10% increase in global accuracy for both trainees and fully trained gastroenterologists [89].…”
Section: Trainingmentioning
confidence: 99%
“…Recommendations suggest that training programs can help in achieving a high accuracy and good interobserver agreement in the use of AEITs such as NBI, and that it is a requirement for use in clinical practice [1, 2, 33, 86-88]. Even for simple NBI patterns in the stomach, a learning curve was observed, with a 10% increase in global accuracy for both trainees and fully trained gastroenterologists [89].…”
Section: Trainingmentioning
confidence: 99%
“…In lower GI endoscopy, multiple studies have shown that both experienced endoscopists as trainees have a rapid learning curve for the detection and characterization of colorectal polyps with VC, not only in still images but also in real-time endoscopy [21][22][23][24][25][26][27][28][29] (Figure 1). Studies assessing the learning curve for optical diagnosis in still images showed impressive curves after a short training session; a diagnostic accuracy of at least 89% was reported in all studies and the durability of this gained competency seems to be at least three months.…”
Section: Implications For Patient Carementioning
confidence: 99%
“…Studies assessing the learning curve for optical diagnosis in still images showed impressive curves after a short training session; a diagnostic accuracy of at least 89% was reported in all studies and the durability of this gained competency seems to be at least three months. 23,[25][26][27][28]30 In contrast, Ladabaum et al evaluated community endoscopists' performance in using NBI for the prediction of colorectal diminutive polyp histology, first in still images after a computerized self-learning program and then during real-time colonoscopy. 3 In total, 91% of participants reached 90% accuracy in the ex vivo part of the study.…”
Section: Implications For Patient Carementioning
confidence: 99%
“…Of these, 16 papers [4,[14][15][16][17][18][19][20][21][22][23][24][25][26][27][28] (before 2010 n = 1, 2010-2015 n = 7, 2016-2019 n = 8) matched the selection criteria and were included in the systematic review. Of these studies, seven were from Europe [4,17,21,23,[26][27][28], six from North America [14,16,[18][19][20], 24] and three from Asia [15,22,25]. Among included studies, eight reported on didactic training [4, 14-16, 18, 22, 23, 27], seven on computer-based self-training [17,[19][20][21][24][25][26] and one on computer-based self-training vs. didactic training [28].…”
Section: Study Selection and Characteristicsmentioning
confidence: 99%